2017
DOI: 10.1103/physreve.96.032128
|View full text |Cite
|
Sign up to set email alerts
|

Additional energy-information relations in thermodynamics of small systems

Abstract: The Clausius inequality (CI) form of the second law of thermodynamics relates information changes (entropy) to changes in the first moment of the energy (heat and indirectly also work). Are there similar relations between other moments of the energy distribution, and other information measures, or is the Clausius inequality a one of a kind instance of the energy-information paradigm? If there are additional relations, can they be used to make predictions on measurable quantities? Changes in the energy distribu… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 55 publications
0
23
0
Order By: Relevance
“…[40] (see also Refs. [41,42] for similar analysis), where isothermal processes are constructed by means of alternating infinitesimal adiabatic and isochoric processes in an infinite sequence. Similarly, we assume, here, an infinite sequence of maps E 1 • E 2 • · · · • E N , with N → ∞, each of them describing an infinitessimal time step of the dynamics, with E n (ρ n−1 ) = ρ n , and the Hamiltonian changing as H n−1 → H n , where we set H N ≡ H.…”
Section: Discussionmentioning
confidence: 99%
“…[40] (see also Refs. [41,42] for similar analysis), where isothermal processes are constructed by means of alternating infinitesimal adiabatic and isochoric processes in an infinite sequence. Similarly, we assume, here, an infinite sequence of maps E 1 • E 2 • · · · • E N , with N → ∞, each of them describing an infinitessimal time step of the dynamics, with E n (ρ n−1 ) = ρ n , and the Hamiltonian changing as H n−1 → H n , where we set H N ≡ H.…”
Section: Discussionmentioning
confidence: 99%
“…With this combination of system information and observables, the CI neatly expresses the energyinformation relation that appears in fundamental processes such as Landauer's erasure, the Szilard engine, and reversible state preparation [25,26]. When extending the CI it is desirable to maintain this information-expectation value structure.…”
Section: A Clausius Inequality In Microscopic Setupsmentioning
confidence: 99%
“…See Ref. [26] for an extension of the second law that preserves the information-observable structure, and Refs. [9,10] for an extension that does not.…”
Section: A Clausius Inequality In Microscopic Setupsmentioning
confidence: 99%
“…To define the heat capacity of a small bath we consider two additional macroscopic baths at temperatures T and d ¢ = + T T T. We first thermalize the small bath by connecting it to the large bath at temperature T. This is repeated for bath T′. The heat flow Q (which is equal to the change in the energy of the small bath) is recorded and the small bath heat capacity is given by (8). Note that this process is an isochore (constant volume) since we did not change the energy levels of the small bath (no work involved, only heat).…”
Section: Appendix a Heat Capacity Of Small Bathsmentioning
confidence: 99%
“…Apart from the practical importance of understanding and experimenting with thermodynamics at the smallest scales, the study of quantum thermodynamics has also provided exciting theoretical developments. As an example, it has been shown that there are additional second law-like constraints on small systems interacting with a thermal bath [6][7][8]. In addition, there are thermodynamic effects in heat machines that can be observed only in systems that are sufficiently 'quantum' [9][10][11][12].…”
mentioning
confidence: 99%